Duration of day-care attendance and acute respiratory infection - Fuchs Sandra Costa; Maynart Rita de Cássia; Costa Lenara Ferreira da; Cardozo Adriana; Schierholt Rejane (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1996)
Day-care attendance accounts for an increased frequency of acute respiratory infections (ARI), in numbers of both episodes and hospitalizations. In addition to day-care exposure, risk factors include age, siblings, and crowding. The purpose of this study was to investigate a possible association between duration of day-care exposure and ARI. A cross-sectional study was carried out to compared ARI rates for children exposed to day care and children cared for at home. Children with at least one parent working in a hospital were sampled from the hospital-run day-care center and those cared for at home. An acute respiratory infection was defined as the presence of two or more signs or symptoms in the previous two weeks. Children exposed to the day-care center for 12 to 50 hours a week had a three to five times greater risk of developing ARI than those staying at home. This risk was assessed independently, taking socioeconomic status, age, and number of siblings into account. Risk of respiratory illness and day-care attendance has been described elsewhere, but this study presents original findings related to duration of exposure. With a view towards reducing risk of ARI, improvements should be made in institutional day-care centers in Brazil, where family day care is still not available.